1999
DOI: 10.1146/annurev.ento.44.1.317
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Physiological Phase in Insects

Abstract: Insects respond to crowding in a variety of ways that are usually exemplified by rapid changes in behavior and culminate in enduring long-term morphological and/or chromatic responses. A common feature of both short-term and long-term effects is that they are graded, dependent not only on density but also on the duration and on phase history of the maternal generation. Because of their exoskeletons, which are persistent for the duration of each instar and endure throughout adult life, overt changes in morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
154
2
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(161 citation statements)
references
References 133 publications
3
154
2
2
Order By: Relevance
“…The major behavioral characteristic of gregarious-phase locusts is their strong attraction to conspecifics, which translates into active aggregation behavior (Ellis, 1959(Ellis, , 1963Uvarov, 1966). The phase transformation is thought to be a positive feedback process, with changes in behavior preceding and facilitating other phasechanges including biochemical, physiological, and morphological ones (Pener, 1991;Pener and Yerushalmi, 1998;Applebaum and Heifetz, 1999;Pener and Simpson, 2009). Recent findings have identified the primary sensory inputs inducing a densitydependent phase change in locusts .…”
Section: Introductionmentioning
confidence: 99%
“…The major behavioral characteristic of gregarious-phase locusts is their strong attraction to conspecifics, which translates into active aggregation behavior (Ellis, 1959(Ellis, , 1963Uvarov, 1966). The phase transformation is thought to be a positive feedback process, with changes in behavior preceding and facilitating other phasechanges including biochemical, physiological, and morphological ones (Pener, 1991;Pener and Yerushalmi, 1998;Applebaum and Heifetz, 1999;Pener and Simpson, 2009). Recent findings have identified the primary sensory inputs inducing a densitydependent phase change in locusts .…”
Section: Introductionmentioning
confidence: 99%
“…The most obvious examples are those where there are distinct polyphenismsFfor example in the locust, which may 'choose' at the larval stage to develop as either a solitary or a migratory morph based on tactile or pheromonic signals that indicate population density and food availability. 12 Such morphs are very different anatomically, behaviorally and physiologically. Generally, however, adaptive developmental plasticity produces a more continuous range of phenotypes.…”
Section: Developmental Processesmentioning
confidence: 99%
“…He played a principal role in the field of locust reproduction: he and his colleagues isolated the oocyte protein vitellogenin Lubzens et al, 1981;Asher et al, 1983) and identified the physiological mechanisms that regulate and mediate its production and action. Dr. Applebaum was also intrigued by the locust phase transition-physiological changes that are expressed in coloration, morphology, developmental rate, metabolism, and behavior in response to increased population density (Applebaum and Heifetz, 1999)-and carried out important research into the mechanism of this phenomenon (Heifetz et al, 1996;Applebaum et al, 1997;Heifetz et al, 1997). His interest in insect hormones, such as juvenile hormone, diuretic hormone, and adipokinetic hormone, produced important results (Pines et al, 1981;Gadot et al, 1987;Applebaum et al, 1990;Zhou et al, 2000) and led to a breakthrough in juvenile hormone research in Drosophila (Richard et al, 1989).…”
mentioning
confidence: 99%